Prospective study of pulmonary hypertension in preterm infants with bronchopulmonary dysplasia. Issue 2 (14th December 2018) - Vayalthrikkovil, Sakeer; Vorhies, Erika; Stritzke, Amelie; Bashir, Rani A.; Mohammad, Khorshid; Kamaluddeen, Majeeda; Thomas, Sumesh; Al Awad, Essa; Murthy, Prashanth; Soraisham, Amuchou
Abstract: Objective: To evaluate the prevalence, risk factors, and optimal timing of echocardiogram for pulmonary hypertension (PH) in infants with bronchopulmonary dysplasia (BPD). Design: In this prospective study, infants with gestational age (GA) <30 weeks admitted to a tertiary NICU between July 2015 and June 2017 who required positive pressure ventilation or oxygen therapy at ≥28 days of life were evaluated with serial echocardiograms at study enrollment (4‐6 weeks of age), 32 weeks (only for ≤25 weeks), 36, and 40 weeks post‐menstrual age (PMA) for PH. Results: Of 126 infants (mean birth weight 858 ± 221 g; mean GA 26.1 ± 1.6 wks), 48 (38%) developed PH at any time during their hospital stay. The first study echocardiogram was performed at a median age of 31 weeks PMA. The prevalence of PH was 36/126 (28.5%) at enrollment, at 6/30 (20%) at 32 weeks, 24/111 (21.6%) at 36 weeks, and 10/59 (17%) at 40 weeks. No new cases of PH were identified at 40 weeks. At 36 weeks, none of the infants with mild BPD had PH, whereas 20% of moderate and 32% of severe BPD infants had PH. After controlling for confounding variables severe BPD (OR 3.31, 95%CI 1.12, 9.74), and ventilator associated pneumonia (VAP) (OR 17.9, 95%CI 3.9, 82.11) remained independent risk factors for BPD‐associated PH. Conclusion: Echocardiographic screening for PH can be safely restricted to infants with moderate or severe BPD at 36 weeks PMA. We identified VAP as an independent risk factor for PH.